PENGARUH PENGETAHUAN, SIKAP PENDERITA TUBERKULOSIS PARU DAN KONDISI RUMAH TERHADAP PENCEGAHAN PENULARAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS DESA LAMA KABUPATEN LANGKAT - hasanah, nur (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2022)
ABSTRACT Tuberculosis is an infectious disease caused by the bacteria directly tuberculosis ( Mycobacterium tuberculosis ) , and estimated about a third of the world population has been infected by Mycobacterium tuberculosis , the WHO said 22 countries with the burden of tuberculosis ( TB ) in the world's highest 50 % of them come from countries Africa and Asia , and the Americas ( Brazil ) , assuming the prevalence of acid-fast bacilli ( AFB ) ( + ) in Indonesia is estimated to patients was 130 per 100,000 population , based on data from The District health KabupatenLangkat , desa lama  health center ranks first pulmonary TB disease , in in 2011 , there were 91 cases ( AFB ( ( + ) , in 2012 increased to 138 cases with ( BTA ) ( + ) . 's type is analytical study using a cross-sectional study design that aims to find pengaruh.pengetahuan , attitude TB pulmonary and housing conditions on the prevention of transmission of TB . research was carried out in the region of the Old Village district health centers Langkat , the population was all patients with pulmonary TB 138 people with a sample of 43 respondents . The results showed that there is a relationship between the knowledge of TB transmission precautions obtained p value = 0.000 with OR = 25.667 , attitudes precautions obtained with p value = 0.001 means that there is a meaningful relationship between gesture with OR = 12.824 , residential density with precautions can p value = 0.041 with OR = 5.417 , extensive ventilation with pulmonary TB transmission precautions obtained p value = 0.042 with OR = 4.622 , dominant variable effect on the prevention of pulmonary TB transmission is the attitude with p = 0.043 with OR = 11.494. For the Department of Health in collaboration with health centers in an effort to improve the quality of care specifically about the health status of pulmonary TB disease .